Trust Property: Legal Aspects - Safonchyk, Oksana; Hlyniana, Kateryna; Mazurenko, Svetlana (Cuestiones Políticas, 2020)
The article is devoted to the history of the emergence and formation of the institution of trust property in relation to various legal systems. The purpose of such a historical analysis of the institution of trust property is to find a possible place of this legal institution in domestic law, because trust property is a relatively new legal construct for Ukrainian law. The relevance of the article is to study the possibility of using the Anglo-American Trust Institute in Ukraine. The object of the study of this article is the legal relations arising from the institute of trust property. Methods of historicism, method of logic, method of analysis, method of synthesis, method of systematic research, and comparative-legal method were used in the study. The authors concluded that the institution of trust property goes back to one of the branches of English law. At the same time, the institution of trust is not inherent in the domestic legal system. However, since the 1990s, the domestic legislator has tried several times to introduce the relevant institution into Ukrainian legislation. So far, all of these attempts have failed.